1999
DOI: 10.1046/j.1365-2141.1999.01232.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective molecular study of chimaerism in patients with haematological malignancies receiving unrelated cord blood or bone marrow transplants: detection of mixed chimaerism predicts graft failure with or without early autologous reconstitution in cord blood recipients

Abstract: We prospectively studied the chimaerism status in the bone marrow (BM) and peripheral blood (PB) of 23 patients receiving umbilical cord (UCB, 14 cases) or BM (nine cases) transplants from unrelated donors by PCR amplification of four individual-specific VNTR genetic loci. Haematological engraftment, with persistent full donor pattern. was observed in 10/14 (72%) patients receiving UCB and in 9/9 (100%) patients transplanted with marrow from an unrelated donor (MUD). In contrast, the remaining four patients co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Our observation is in keeping with those made in these patients who received other unmanipulated HSC grafts. [26][27][28] Mixed chimerism was found in two of our leukemia patients and both went on to GF. Monitoring chimerism at short time intervals helped to identify the course of these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observation is in keeping with those made in these patients who received other unmanipulated HSC grafts. [26][27][28] Mixed chimerism was found in two of our leukemia patients and both went on to GF. Monitoring chimerism at short time intervals helped to identify the course of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring chimerism at short time intervals helped to identify the course of these patients. Cimino et al 28 showed that mixed chimerism in UCBT recipients before day 35 predicted GF, with or without autologous reconstitution; and a high probability of leukemia relapse. Patients with nonmalignant disorders 26,29 and those who have not received recent chemotherapy 18 are more likely to develop mixed chimerism after HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…39 Rejection may be heralded by incomplete and decreasing donor chimerism, allowing the re-expression of host T cell function. [40][41][42][43] Graft dysfunction is an ominous circumstance and may herald relapse of neoplasm with restoration of host hematopoiesis. [44][45][46] …”
Section: Factors Influencing Graft Dysfunctionmentioning
confidence: 99%
“…The details on this finding have been reported and extensively discussed elsewhere. 23 The Minnesota group observed autologous hematopoietic recovery in four of 102 patients of its series, but this phenomenon was restricted to patients affected by nonmalignant diseases and followed a secondary graft failure after a primary engraftment. 11 The spontaneous and primary autologous hematopoietic reconstitution occurring early after CBT in leukemic patients conditioned with a highly intensive regimen has been anecdotically reported.…”
Section: Discussionmentioning
confidence: 99%
“…Chimerism studies were performed on BM and peripheral blood cells at days 20, 35, 60, 100, 180, 270 and 365 after transplant. 23 Engraftment with full chimerism required myeloid hematopoietic recovery with all cells in the recipient of donor origin, while the simultaneous presence of donor and recipient cells was defined as engraftment with mixed chimerism. The absence of hematopoietic recovery at 90 days after transplant and the autologous hematopoietic reconstitution were considered as engraftment failure.…”
Section: Hematopoietic Recovery Chimerism and Engraftmentmentioning
confidence: 99%